Introduction to structural analysis : displacement and force methods - Mau, S. T. (CRC Press, 2012)
"Bridging the gap between what is traditionally taught in textbooks and classrooms and what is actually practiced in engineering firms, this indispensible text clearly and linearly details every solution method in the framework of the traditional Force Method and the matrix displacement method of analysis. It covers influence lines, non-prismatic members, composite structures, secondary stress analysis, and the limits of linear and static structural analysis. Integrating classical and modern methodologies, it explains complicated analysis using simplified methods and numerous examples and provides an understanding of the underlying methodologies of finite element analysis"--